(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
In the article, the distribution and systematic place of the tall aquatic plant Pistia in nature is determined. The role of the pistachio plant in the treatment of wastewater from poultry factories, piggery complexes and hemp processing plants is very high